2022
DOI: 10.1101/2022.08.15.503206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteome-scale induced proximity screens reveal highly potent protein degraders and stabilizers

Abstract: Targeted protein degradation and stabilization are promising therapeutic modalities due to their potency and versatility. However, only few E3 ligases and deubiquitinases have been harnessed for this purpose. Moreover, there may be other protein classes that could be exploited for protein stabilization or degradation. Here, we used a proteome-scale platform to identify hundreds of human proteins that can promote the degradation or stabilization of a target protein in a proximity-dependent manner. This allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 147 publications
0
16
0
Order By: Relevance
“…The low efficacy of GID4 compared to VHL and CRBN in this assay may reflect a higher intrinsic activity of the VHL and CRBN E3 complexes or assay parameters including effector-vhhGFP expression levels, catalytic access to lysine residues in EGFP, the geometry of substrate reporter fusions (Nversus C-terminal tagging), and/or efficiency of E3 effector fusion incorporation into multi-subunit E3 ligases. 22,23 Nonetheless, this result demonstrated that GID4 can target ectopically recruited substrates for degradation and provided a rationale for our subsequent efforts to develop small molecule binders to GID4.…”
Section: ■ Introductionmentioning
confidence: 90%
“…The low efficacy of GID4 compared to VHL and CRBN in this assay may reflect a higher intrinsic activity of the VHL and CRBN E3 complexes or assay parameters including effector-vhhGFP expression levels, catalytic access to lysine residues in EGFP, the geometry of substrate reporter fusions (Nversus C-terminal tagging), and/or efficiency of E3 effector fusion incorporation into multi-subunit E3 ligases. 22,23 Nonetheless, this result demonstrated that GID4 can target ectopically recruited substrates for degradation and provided a rationale for our subsequent efforts to develop small molecule binders to GID4.…”
Section: ■ Introductionmentioning
confidence: 90%
“…In other instances, the result of induced proximity can be an emerging effect where one protein partner is endowed with a novel, neomorphic function. 4 This scenario is best illustrated by smallmolecule degraders that recruit proteins of interest (POIs) to an E3 ligase. The change in E3 ligase interactome consequently leads to ubiquitination and degradation of the POI, which it would not recognize in the absence of the small molecule.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chemically inducing proximity between two target proteins is an established mechanism of action of natural products as well as synthetic small molecules, and has expanded to clinical applications. In some instances, drug-induced proximity results in a functional inhibition of one participating protein via steric confinements imposed by the other effector. In other instances, the result of induced proximity can be an emerging effect where one protein partner is endowed with a novel, neomorphic function . This scenario is best illustrated by small-molecule degraders that recruit proteins of interest (POIs) to an E3 ligase.…”
Section: Introductionmentioning
confidence: 99%
“…In some instances, drug-induced proximity results in a functional inhibition of one participating protein via steric confinements imposed by the other effector. In other instances, the result of induced proximity can be an emerging effect where one protein partner is endowed with a novel, neomorphic function 4 . This scenario is best illustrated by small-molecule degraders that recruit proteins of interest (POIs) to an E3 ligase.…”
Section: Introductionmentioning
confidence: 99%